2018
DOI: 10.1111/1468-0106.12253
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Japan’s negative interest rate policy on Asian financial markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Hanisch (2017) bases his research on a structural dynamic factor model with sign restrictions for Japan and argues a significant impact on goods and stock prices. Moreover, Fukuda (2018) finds that Japan's long-term interest rate decline had significantly positive effects on Asian stock prices in the NIRP period.…”
Section: Asset Prices and Foreign Exchanges Rates As Intermediate Targets In Unconventional Monetary Policy Channelsmentioning
confidence: 99%
“…Hanisch (2017) bases his research on a structural dynamic factor model with sign restrictions for Japan and argues a significant impact on goods and stock prices. Moreover, Fukuda (2018) finds that Japan's long-term interest rate decline had significantly positive effects on Asian stock prices in the NIRP period.…”
Section: Asset Prices and Foreign Exchanges Rates As Intermediate Targets In Unconventional Monetary Policy Channelsmentioning
confidence: 99%
“…Fukuda () shows that NIRP appear to constrain the equity market spillovers from Japan to Asian economies, whereas Feldkircher, Huber, Chantapacdepong, and Punzi () document that NIRP have an amplifying impact on interest rate spillovers. Spiegel and Tai () find that monetary policy shocks under NIRP affect the Japanese economy, as predicted by standard transmission channels.…”
mentioning
confidence: 99%
“…In this framework, the BoJ also allows for NIRP. Fukuda (2018) investigated the impact of the BoJ's NIRP on Asian financial markets and showed that it might have benefitted Asian economies through the positive effects on Asian stock prices. Angrick and Nemoto (2017) provided an overview of the operational implementation of NIRP in Europe and Japan.…”
Section: Introductionmentioning
confidence: 99%